Constructing a matriarchal society through nego-feminism in the works of Zaynab Alkali - Muhammad, Usman Ambu (2018)
Women’s discrimination has been a long and nagging issue pervading both Western and African societies. Starting from the literary history of the West, covering the eras of Mary Wollstonecraft, Elizabeth Cady Stanton, Susan B. Anthony, and Simone de Beauvoir to current feminists there have been many movements that aimed to eradicate women’s subjugation by patriarchal structures. The same problem exists in African societies. Women in sub-Saharan Africa suffer human rights violations. Females suffer sexual discrimination, violence, political marginalization and economic deprivation. The objective of this research is to examine the condition and treatment of women in the patriarchal society represented in the works of Zaynab Alkali. Another objective is to show how Zaynab Alkali reconstructs the role of women through negotiation in her novels. Finally, this research determined ways in which nego-feminism can be used as a tool to bridge the gender gap that exists in the African society in Zaynab Alkali’s novels. The methodology utilised textual analyses of Zaynab Alkali’s novels. The analyses were carried out in relation to the tenets of negofeminism theory and cultural theory. The findings of this study show that the construction of a matriarchal society played a significant role in uplifting the female characters in Zaynab Alkali’s novels. The findings also reveal that nego-feminism could be used as a tool for bridging the gap between the sexes in the type of society represented in Zaynab Alkali’s novels., This study succeeded in discussing feminism historically from both Western and African perspectives and the problems with these perspectives vis-a-vis their associated achievements.